Microbial Communities in Volcanic Glacier Ecosystems - Garcia-Lopez, Eva; Ruiz-Blas, Fatima; Sanchez-Casanova, Silvia; Peña Perez, Sonia; Martin-Cerezo, Maria Luisa; Cid, Cristina (Frontiers in Microbiology, 2022)
Glaciers constitute a polyextremophilic environment characterized by low temperatures, high solar radiation, a lack of nutrients, and low water availability. However, glaciers located in volcanic regions have special characteristics, since the volcanic foci provide them with heat and nutrients that allow the growth of microbial communities highly adapted to this environment. Most of the studies on these glacial ecosystems have been carried out in volcanic environments in the northern hemisphere, including Iceland and the Pacific Northwest. To better know the microbial diversity of the underexplored glacial ecosystems, and to check what their specific characteristics were, we studied the structure of bacterial communities living in volcanic glaciers in Deception Island, Antarctica, and in the Kamchatka peninsula. In addition to geographic coordinates, many other glacier environmental factors (like volcanic activity, altitude, temperature, pH, or ice chemical composition) that can influence the diversity and distribution of microbial communities were considered in this study. Finally, using their taxonomic assignments, an attempt was made to compare how different or similar are the biogeochemical cycles in which these microbiomes are involved.